Thematic Learning Models in Competence Body Massage Solus Per Aqua in Vocational Education Institutions - Saputri, Nurulisma; Khumaedi, Muhammad; Supraptono, Eko Supraptono (Universitas Negeri Semarang, 2019)
This research is motivated by knowing the lack of usingthe thematic learning models in Vocational Education Institutions. This study aims to: Generate a thematic learning model ensure valid, reliable, feasible and effective on the solus per aqua body competency in vocational high school. This research used research and development (R&D) methods. To obtain the validity and reliability of the contents on learning models and thematic textbooks, I used CVR and kappa coefficients, the feasibility test applied a Likert scale of four score criteria, while to test the effectiveness of the improvement on the learning outcomes within the thematic learning model using an independent t-test.The results showed that the contents validation on the learning model and textbooks has obtained from 2 assessors. They declared valid category values and reliability, the results of the effectiveness on improving the learning outcomes within the thematic models showed that the t-test 14,489 was effectively used. The conclusion is that the thematic learning model on valid body massage solus per aqua competence (Spa) is reliable, feasible and effective so that it can be used at vocational high schools.Thematic learning can be implemented by teachers as an appropriate learning strategy through combining the material of several subjects with thematic textbooks to create fun learning. At accordance with this finding useful as curriculum alignment and thematic learning innovations, they can be applied at vocational education institutions.